The effect of bi-axial behaviour of mechanical anchors on the lateral response of multi-panel CLT shearwalls. (1st December 2020) - Masroor, Mohammad; Doudak, Ghasan; Casagrande, Daniele
Highlights: Elastic-plastic analytical methods of multi-panel CLT shearwalls are investigated. The contribution of bi-axial angle brackets and hold-downs are considered. Sensitivity analysis is carried out to measure the effect of bi-axial angle brackets. The methods are validated using published experimental tests. Abstract: The importance of the bi-axial behaviour of some types of hold-downs and angle brackets has recently been identified, highlighting the need to include such effect in the analysis and design of Cross-Laminated Timber (CLT) shearwalls. The current study investigates elastic-plastic analytical methods for multi-panel CLT shearwalls, including the bi-axial contribution of the angle brackets and hold-downs connections and proposes expression in the elastic region to establish the Coupled-Panel (CP) and Single-Wall (SW) kinematic behaviours of the shearwall. The results from the elastic analysis show that considering the bi-axial effect of the angle brackets leads to more panels maintaining contact with the ground and resulting in less displacements and rotations. Sensitivity analyses are conducted to investigate the influence of the bi-axial contribution of the angle brackets. The proposed methodologies are verified using a numerical model, and the results showed that the analytical solution matches that obtained from the numerical model almost perfectly. Also, the methods are validated by comparing them with published experimental test results, and a reasonable match is obtained.